'Open-and-close' pituitary surgery in an acromegalic man presenting with excessive sweatiness. (9th June 2016) - Cheung, Kitty Kit Ting; Chow, Francis Chun Chung; Lo, Anthony Wing Ip
Abstract : Ectopic-acromegaly is rare. Diagnosing ectopic-acromegaly is challenging given that the clinical and biochemical manifestations can be almost indistinguishable from those of patients with growth hormone secreting pituitary adenomas. This case report highlights the importance of clinical vigilance in differentiating between the two conditions. A 41-year-old Caucasian man presented with typical features of acromegaly with an enlarged pituitary and a lung lesion. Although excision of the lung mass showed a carcinoid tumour, normalisation of growth hormone factors did not occur soon enough. This led to a presumed diagnosis of a pituitary adenoma. However, no pituitary tumour was identified during trans-sphenoidal surgery. Postoperatively, the patient improved clinically and biochemically. Retrospective histological examination of the excised lung lesion showed a small proportion of tumour cells containing growth hormone releasing hormone (GHRH), suggesting ectopic-GHRH production from the lung neuroendocrine tumour. An open-and-close trans-sphenoidal surgery could have been avoided in this patient with ectopic-GHRH acromegaly.